2001
DOI: 10.2460/javma.2001.218.900
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and immunogenicity of a modified-live equine influenza virus vaccine in ponies after induction of exercise-induced immunosuppression

Abstract: Results suggested that administration of this MLV vaccine to ponies with exercise-induced immunosuppression was safe and that administration of a single dose to ponies provided clinical protection 3 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 15 publications
3
41
0
2
Order By: Relevance
“…; Heska Corp.) has shown more promising results. Efficacy trials of this vaccine showed animals were clinically protected 3 months after vaccination (14) and had reduced severity of disease with significant clinical protection 6 months after vaccination (35).…”
mentioning
confidence: 99%
“…; Heska Corp.) has shown more promising results. Efficacy trials of this vaccine showed animals were clinically protected 3 months after vaccination (14) and had reduced severity of disease with significant clinical protection 6 months after vaccination (35).…”
mentioning
confidence: 99%
“…vaccine; Intervet) has been developed for horses and is available commercially in North America (53). Field experience with both the human and the equine live influenza vaccines have demonstrated the safety, effectiveness, and genetic and phenotypic stability of these vaccine platforms (7,8,11,14,41,53,56,65,67).…”
mentioning
confidence: 99%
“…Robson et al (2003) encontraram neutrofilia e linfopenia evidentes uma hora e um dia após enduro de 80km, retornando à normalidade somente três dias após, como ocorreu no presente estudo. Alguns autores (Kurcz et al, 1998;Lunn et al, 2001), que trabalharam com cavalos em esteira rolante de alta velocidade, encontraram supressão da resposta proliferativa de linfócitos, porém Cywińska et al (2012) encontraram diminuição dessa resposta somente em cavalos de longa distância (160km) e não nos cavalos de regularidade.…”
Section: Resultsunclassified